Battles that Changed History : Fifty Decisive Battles Spanning Over 2,500 Years of Warfare - Regan, Geoffrey (Rawalpindi Services Book Club, 2008)
Offers an account of 50 decisive battles that have had a long-term impact on the course of world history. Using maps and illustrations, this work not only examines the background and consequences of each battle, but also re-creates the intense fighting, analyses the tactics and profiles key commanders and weaponry used.
Include Color Illustrations, Maps and Index
Keywords: Battles -- Military history